Penentu Harga Saham pada Perusahaan Terdaftar di Jakarta Islamic Index (JII) - Ratna Ayu Widyastuti; Edi Susilo (Universitas Islam Nahdlatul Ulama Jepara, 2020)
The research objective is to analyze the effect of Return on Equity (ROE), Earning per Share (EPS), Inflation, and Exchange Rates on the Jakarta Islamic Index stock price, 2015-2018. This research is a quantitative study, using secondary data published on the Indonesia Stock Exchange. There are 45 companies listed on the JII index which are made population. The sampling technique used purposive sampling, and there were 17 companies sampled, based on the criteria. Data analysis used multiple linear regression, with the SPSS program version 20. The results of the study, the variable Return on Equity (ROE) and Earning per Share (EPS) partially had a positive and significant effect on stock prices, while the Inflation variable and the exchange rate partially has no effect on stock prices. Simultaneously, Return on Equity (ROE), Earning per Share (EPS), Inflation, and Exchange Rate affect stock prices.